Assessment of the quality of fresh nixtamalized maize doughs with different degrees of cooking and milling: A comparison of Mixolab and RVA analyses. (November 2021) - Espinosa-Ramírez, Johanan; De la Rosa-Millan, Julián; Pérez-Carrillo, Esther; Serna-Saldívar, Sergio O.
Abstract: Fresh nixtamalized maize dough (NMD) is commonly preferred by producers as raw material for the manufacture of a diversity of nixtamalized products. Based on the application, NMD may have different particle size distributions that may limit their analysis by common methods such as RVA. In the present study, we used the Mixolab to analyze fresh NMD produced with three degrees of cooking (undercooked, adequate cooked and overcooked) and milled to produce coarse, intermediate and fine doughs. Results were correlated with starch and tortilla features in order to evaluate the prediction of pregelatinization and starch damage occurring during processing, and with the quality of the final product. RVA was used for comparison purposes. Unlike RVA curves, Mixolab showed defined peak viscosities during heating independently of the milling degree of samples. Moreover, the Mixolab parameters showed strong correlations with the starch thermal properties, crystallinity, starch damage and lixiviated amylose. More correlations were obtained among Mixolab and RVA parameters in relationship with the attributes of tortillas. Results validated that the Mixolab is an efficient and rapid strategy to discern among different cooking degrees of fresh NMD independently of the particle size distribution, and may be useful to predict the quality of tortillas. Graphical abstract: Image 1 Highlights: Mixolab discerns among different degrees of cooking in nixtamalized maize doughs (NMD). The milling degree did not affect the Mixolab profile. Mixolab parameters were strongly correlated with starch damage in NMD. Mixolab showed more correlations with starch and tortilla features compared to RVA. Mixolab resulted an adequate method to evaluate the quality of fresh NMD.